CD4:CD8 ratio in children with perinatally acquired HIV‐1 infection1. Issue 9 (6th August 2018) - Seers, T; Vassallo, P; Pollock, K; Thornhill, JP; Fidler, S; Foster, C
Abstract : Objectives: In adults with horizontally acquired HIV infection, an inverted CD4:CD8 ratio is associated with persistent immune activation, size of HIV reservoir and predicts an increased risk of non‐AIDS‐defining adverse events. Normalization of this ratio with antiretroviral therapy (ART) is suboptimal in adults, despite viral suppression, and is less well described in paediatric populations. We investigated rates of CD4:CD8 ratio recovery in children with perinatally acquired HIV infection (PaHIV) on ART. Methods: A cross‐sectional, retrospective analysis of routine clinical data in children with PaHIV (5–18 years old) attending a single UK centre was carried out. Results: CD4:CD8 normalization was seen in 62% of children on suppressive ART. A negative correlation was found between current CD4:CD8 ratio and age at start of ART. Positive correlations were found between current CD4:CD8 ratio and total time with suppressed HIV viral load and nadir CD4 counts. Multiple linear regression analysis showed that age at start of ART was significantly associated with current CD4:CD8 ratio (standardized β = −0.680; P < 0.001). Patient sex, ethnicity and antiretroviral regimen did not affect ratio recovery. Conclusions: We found higher rates of CD4:CD8 ratio normalization compared with previous adult studies. Children who started ART at a younger age were more likely to recover a normal ratio. The current policy of universal treatment for all HIV‐positive adults and children will enhance immunological normalization.